How autonomous is the autonomy of will? Considerations based on several peruvian constitutional court´s judgments - Cárdenas Krenz, Ronald (2022)
The article deals with the autonomy of the will, analyzing its nature and limits, based on the review of some sentences of the Peruvian Constitutional Court on the subject of freedom, raising the need to promote a culture of freedom hand in hand of a culture of responsibility, as an ethical and bioethical response to fundamental debates of our time.